2022
DOI: 10.1038/s41598-022-25758-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of a cellular exercise model based on electrical pulse stimulation

Abstract: Skeletal muscle communicates with other organs via myokines, which are secreted by muscle during exercise and exert various effects. Despite much investigation of the exercise, the underlying molecular mechanisms are still not fully understood. Here, we applied an in vitro exercise model in which cultured C2C12 myotubes were subjected to electrical pulse stimulation (EPS), which mimics contracting muscle. Based on the significantly up- and down-regulated genes in EPS, we constructed an in silico model to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…We have previously argued that the EPS model mimic exercise quite well, at least when it comes to metabolic effects ( Nikolic et al, 2017 ). Recently, a comparative analysis of exercise signature genes in skeletal muscles after in vivo exercise and in vitro EPS also confirmed that the EPS model mimicked in vivo exercise at the transcriptome level ( Lee et al, 2022 ). Altogether, the EPS model of human myotubes appears to be useful and relevant.…”
Section: Discussionmentioning
confidence: 80%
“…We have previously argued that the EPS model mimic exercise quite well, at least when it comes to metabolic effects ( Nikolic et al, 2017 ). Recently, a comparative analysis of exercise signature genes in skeletal muscles after in vivo exercise and in vitro EPS also confirmed that the EPS model mimicked in vivo exercise at the transcriptome level ( Lee et al, 2022 ). Altogether, the EPS model of human myotubes appears to be useful and relevant.…”
Section: Discussionmentioning
confidence: 80%
“…Overall, this suggests that NR4A3 has a critical role in SkM metabolism and adaptation to changes in physical activity (23). In addition to NR4A3, amphiregulin (Areg) has been shown to be upregulated after EL-EPS in C2C12 myotubes and in SkM of exercised mice (24) suggesting its´ role as a novel exerkine.…”
Section: D In Vitro Exercise and Transcriptomicsmentioning
confidence: 95%